Intrusion of mandibular primary teeth - Vitug, Jocelyn D. (The Journal of the Philippine Dental Association)
AF, a four year old patient was referred to the Pediatric Dentistry Division by the PCMC-Out Patient Department due to tooth mobility secondary to a fall. She consulted the Out Patient Department a day after the trauma presenting signs of infection.